2012
DOI: 10.1152/ajpregu.00634.2011
|View full text |Cite
|
Sign up to set email alerts
|

Systems genetic analysis of multivariate response to iron deficiency in mice

Abstract: A, Fleet JC, Jones BC. Systems genetic analysis of multivariate response to iron deficiency in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…ID diet also produces peripheral organ (e.g., liver and spleen) iron deficiency and may also produce an anemia in some animals (Yin, et al, 2012), thus raising concerns as to the relevance of peripheral ID effects on the ID effects found in brain. Studies utilizing a broad range of BXD RI mice strains under normal and ID condition have not identified any significant relation between peripheral iron status and VMB iron status (Jellen, et al, 2012; Yin, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ID diet also produces peripheral organ (e.g., liver and spleen) iron deficiency and may also produce an anemia in some animals (Yin, et al, 2012), thus raising concerns as to the relevance of peripheral ID effects on the ID effects found in brain. Studies utilizing a broad range of BXD RI mice strains under normal and ID condition have not identified any significant relation between peripheral iron status and VMB iron status (Jellen, et al, 2012; Yin, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…ID diet also produces peripheral organ (e.g., liver and spleen) iron deficiency and may also produce an anemia in some animals (Yin, et al, 2012), thus raising concerns as to the relevance of peripheral ID effects on the ID effects found in brain. Studies utilizing a broad range of BXD RI mice strains under normal and ID condition have not identified any significant relation between peripheral iron status and VMB iron status (Jellen, et al, 2012; Yin, et al, 2012). In cell culture models, where the issue of anemia or altered peripheral metabolism are not operational, changes in DAergic system with diminished iron concentrations were similar to DAergic system changes seen in ID animal (Connor, et al, 2009; Unger, et al, 2008; Wiesinger, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of iron deficiency in mice has been evaluated [119]. This study revealed that polymorphisms in multiple genes cause individual variations in iron regulation, especially in response to dietary iron challenge.…”
Section: Genetic Polymorphism Of Proteins Involved In Iron Metabolismmentioning
confidence: 99%
“…It also has a primary environmental factor of reduced peripheral iron related both to severity of RLS [39], and when severe with increased RLS prevalence [42] that can be corrected by reversing the iron deficiency [40]. One approach to establishing an animal model of RLS other than disrupting known genes would be to find an inbred mouse strain whose genetics produce the biological findings of RLS when exposed to the primary environmental factor, i.e.…”
Section: 0 Forward Genetics Analysis Identifies a Mouse Strain Thatmentioning
confidence: 99%
“…The VMB iron concentrations for controls varied by about 25% over the strains while the difference between control and ID for each strain varied between 0 and 35% [41]. Moreover there was no correlation between the ID effects on VMB and hemoglobin or other peripheral measures of iron (data from a prior study [42] (see Figure 1). One mouse strain (strain 40 females) showed the biological phenotype of response to iron deficiency producing reduced VMB iron with minimal change in hemoglobin.…”
Section: 0 Forward Genetics Analysis Identifies a Mouse Strain Thatmentioning
confidence: 99%